2020
DOI: 10.3126/jcmc.v10i1.28066
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for self-directed learning among nursing students in a medical college, Chitwan

Abstract: Background: Self-directed learning is a type of instructional strategy where students take charge of their learning process. Self directed learning is learning approach where learners are responsible towards learning which helps students think critically and perform task confidently. The skills that are learned through self-directed learning remain lifelong and helps to provide patient care in effective way and uplifting the nursing profession. This study was conducted to identify the readiness for self-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Similar studies by Ahmad and Batool (2019) and Luo et al (2019) also found a positive and significant relationship between self-directed learning, students' motivation and problem-solving abilities. Other studies that investigated the relationship between self-directed learning, time management and motivation among undergraduate students found positive correlation between these variables (Adib et al, 2019;Durnali, 2020;Ertu g and Faydali, 2018;Singh and Paudel, 2020). In line with the foregoing discussion, a hypothesis was generated and tested as follows:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 93%
“…Similar studies by Ahmad and Batool (2019) and Luo et al (2019) also found a positive and significant relationship between self-directed learning, students' motivation and problem-solving abilities. Other studies that investigated the relationship between self-directed learning, time management and motivation among undergraduate students found positive correlation between these variables (Adib et al, 2019;Durnali, 2020;Ertu g and Faydali, 2018;Singh and Paudel, 2020). In line with the foregoing discussion, a hypothesis was generated and tested as follows:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 93%
“…He concluded that higher a person's cultural intelligence is the higher self-directed learning, self-management and willingness to learn will be. Kim (2014) This was contraindicated with result of, Singh and Paudel (2020) who revealed that, the level of selfdirected learning was significantly associated with age (p=0.036). As well as, Alamurungan and Kumar (2015) showed significant differences in certain scores of selfdirected learning according to demographic and personal characteristics of respondents.…”
Section: Nursing Students Level Of Academic Vitalitymentioning
confidence: 99%
“…indicated that self-directed learning is a very important ability of nurses to solve complex health problems in the fastgrowing and knowledge-incentive healthcare sector.Our study findings are consistent with the findings ofHwang and Oh (2021) who found that higher level of self-directed learning and problem-solving ability of nursing student. Also,Singh and Paudel (2020) found more than two-third of the nursing students were ready for self-directed learning. The mean score of selfcontrol was higher than the mean score of selfmanagement and desire for learning.…”
mentioning
confidence: 96%